2020
DOI: 10.1073/pnas.2003225117
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous polymer dynamics and free volume element size distributions from ultrafast IR spectroscopy

Abstract: A method for measuring the size and size probability distribution of free volume regions in polymeric materials using ultrafast infrared (IR) polarization-selective pump–probe experiments is presented. Measurements of the ultrafast dynamics of a vibrational probe (the CN stretch of phenyl selenocyanate) in poly(methyl methacrylate) show that the probe dynamics are highly confined. The degree of confinement was found to be both time-dependent and dependent on the vibrational frequency of the probe molecule. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
89
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(93 citation statements)
references
References 50 publications
2
89
2
Order By: Relevance
“…Thus, careful analysis of the anisotropy of the restricted reorientation of the vibrating probe molecule provides a size distribution of the FVEs in the polymer or glass sample (9). Hoffman et al (9) carefully compared the FVE distributions from their ROAM analysis with existing measures and found that one of their two models quantitatively agrees with FVEs measured by PALS.…”
Section: How Does Roam Work?mentioning
confidence: 97%
See 4 more Smart Citations
“…Thus, careful analysis of the anisotropy of the restricted reorientation of the vibrating probe molecule provides a size distribution of the FVEs in the polymer or glass sample (9). Hoffman et al (9) carefully compared the FVE distributions from their ROAM analysis with existing measures and found that one of their two models quantitatively agrees with FVEs measured by PALS.…”
Section: How Does Roam Work?mentioning
confidence: 97%
“…The ROAM described by Hoffman et al (9) combines several standard methods of infrared vibrational spectroscopy (14-16), together with a sophisticated analysis to provide information about free volumes in condensed matter. The experimental methods are based on ultrafast vibrational spectroscopy with a femtosecond laser source, thus providing coherent broadband probing with a bandwidth exceeding 100 cm −1 .…”
Section: How Does Roam Work?mentioning
confidence: 99%
See 3 more Smart Citations